Research progress on microbial control techniques of prepared dishes - Xiushan Wang; Pu Jing; Chen Chen; Jinhong Wu; Huiyun Chen; Shunshan Jiao (Food Physics)
Prepared dishes are popular among consumers due to their convenience, but microorganisms in dishes have the potential to cause spoilage and even lead to foodborne illnesses, rendering microbial control a critical step in production. This paper reviews microbial control techniques commonly used in prepared dishes, including conventional thermal techniques; novel thermal processing, including microwave (MW) and radio frequency (RF) heating; and non-thermal treatment, such as high-pressure processing (HPP) and irradiation. In addition, it summarizes the applications of these techniques in prepared dishes and analyzes factors affecting microbial inactivation, providing guidance for the optimization of these techniques. These technologies are compared in terms of technical characteristics, commercial applicability, the dish types for which they are suitable, etc. Traditional thermal treatment is currently the main processing method used for the industrial microbial control of prepared dishes, while other novel processing technologies have their own characteristics. MW has poor penetration ability, RF is suitable for dishes with a regular shape and consistent thickness, HPP (generally 300–600 MPa) is unsuitable for dishes containing air bubbles, and low-dose irradiation (<10 kGy) is preferred only for the pasteurization of prepared dishes due to food safety concerns. Finally, the challenges and countermeasures associated with their application in prepared dishes are discussed. Further studies and continuous improvements of microbial control techniques are of great significance to produce safe and high-quality prepared dishes.